Outbound tourism: why do Malaysians choose South Korea again? - Saad, Mazni; Ramlee, Nur Zafirah; Husin, Nor Azilah; Yulia, Astri (European Publisher Limited, 2022)
This study focuses on the cultural determinants of Malaysian outbound travel to South Korea. The globalization of Korean popular culture and its acceptance was rapidly growing all over the world. The big question is whether this factor also affects the reasons Malaysian travelers in revisiting South Korea. Three-fold objectives were to explore the extent of the intention to revisit South Korea among Malaysian tourists, compare the intention to visit between frequent viewers and infrequent viewers of Korean dramas, and identify contributing factors towards Malaysian tourists’ intention to revisit South Korea. Thus, using the Stimulus Organism Response, the theory explains the effect of the external environment on tourist behaviour through their personal emotion and experience at visited destinations. The findings showed that with a 39% variance explained, Korean rare image, cuisine, and drama had a significant influence on the revisit intention. Hence, tourism stakeholders should seriously promote Malaysia through SDG-11, benchmarking Korean efforts by preserving and conserving culture to maintain a people's integrity and serve as a source of national pride.